2015
DOI: 10.2528/pier15090403
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Harmonic Discontinuous Galerkin Method as a Robust Forward Solver for Microwave Imaging Applications

Abstract: Abstract-Novel microwave imaging systems require flexible forward solvers capable of incorporating arbitrary boundary conditions and inhomogeneous background constitutive parameters. In this work we focus on the implementation of a time-harmonic Discontinuous Galerkin Method (DGM) forward solver with a number of features that aim to benefit tomographic microwave imaging algorithms: locally varying high-order polynomial field expansions, locally varying high-order representations of the complex constitutive par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…as a forward solver to support distinct high-order expansions for the fields, contrasts and contrast sources, but in a full 3D vector-field implementation. Further details on both 2D and 3D DGM-CSI can be found in [38,[57][58][59]. Figure B.1: First stage scenario depicted for a multilayer synthetic phantom in air containing fat (yellow), fibroglandular tissue (blue, "Fibro" = fibroglandular), and a tumour (red).…”
Section: B31 Dgm-csi Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…as a forward solver to support distinct high-order expansions for the fields, contrasts and contrast sources, but in a full 3D vector-field implementation. Further details on both 2D and 3D DGM-CSI can be found in [38,[57][58][59]. Figure B.1: First stage scenario depicted for a multilayer synthetic phantom in air containing fat (yellow), fibroglandular tissue (blue, "Fibro" = fibroglandular), and a tumour (red).…”
Section: B31 Dgm-csi Algorithmmentioning
confidence: 99%
“…To that end, there has been interest in applying contrast enhancement to the modality to bolster its cancer detection and monitoring capabilities, leading to a number of studies of biocompatible substances that alter the gigahertz-range complex electrical permittivity of a tissue of interest, when properly targeted [26,27]. Further details on DGM-CSI can be found in [57,58].…”
Section: A2 Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then for the test case introduced in Section 4, a separation resolution study similar to the one reported in [33] is conducted. We compare the eigenfunction inversion results with the results of a Discontinuous Galerkin Method Contrast Source Inversion (DGM-CSI) algorithm [36]. In addition, for the same test case and three other test cases, results of varying the truncation number N are presented.…”
Section: Contrast Recovery Stage Studymentioning
confidence: 99%